Sprachliche Imitation - Jiddisch in der deutschsprachigen Literatur (18.-20. Jahrhundert) - Schäfer, Lea (Language Variation, 2017)
This book contains a study on fictional, imitated language. In detailed analyses it shows how Jewish figures were characterized through their language in German fiction (18th until early 20th century). It discloses which structures of this fictional language originate from the Yiddish language and which are reflexes of (the author's) orality. At the same time the study contains a comprehensive description of Western Yiddish and its grammatical structures, which are compared with German and Eastern Yiddish varieties.